The Effect of Heating and Postfermentation on Lactoferrin of Fresh and Kefir Goat Milk (Jurnal Ilmu dan Teknologi Hasil Ternak, 2010)
The aim of this study was determinated of lactoferrin profile in goat milk and kefir. The samples were collected from whey raw milk, pasteurized and kefir. Lactoferrin profile in this study consisted of concentration and molecule weight of lactoferrin. Goat lactoferrin was isolated from whey by fractionation on sephadex     G-100 column, it was eluted at 0.1 M phosphate buffer pH 6.8. Characterization of goat lactoferrin by electrophoretic SDS-PAGE techniques detected molecule weight of goat lactoferrin that the isolate of the fractions from fractionation on sephadex G-100 column. Result of the research  showed that pasteurization during storage after fermentation process were influenced by concentration of lactoferrin significant (P<0.05). The molecule weights of lactoferrin in goat milk and kefir were estimated at 84 kDa and 80 kDa. The average concentration of goat lactoferrin at 1.915 mg/ml (without pasteurized), 1.579 mg/ml (pasteurized at 65oC), 0.954 mg/ml (pasteurized at 73oC) and 0.322 mg/ml (pasteurized at 83oC). The average concentration of goat lactoferrin in kefir during storage at 0.663 mg/ml (0 day), 0.448 mg/ml (3  day), 0.249 mg/ml (6 day), 0.142 mg/ml (9 day) dan 0.048 mg/ml (12 day).  Pasteurization at temperature 65oC 30’’ can defend concentration of lactoferrin higher than temperature 73oC 15’’  and temperature 83oC 2’’. Concentration of lactoferrin in kefir were defended until 12 day storage.   Keywords : Lactoferrin, goat milks, kefir